Nitrogen Economy of a Sandy Soil under Groundnut Maize Cropping Sequence at Kuala Brang, Trengganu - Yaacob, Othman (1982)
Groundnut crops have been cultivated on sandy alluvial soil (> 900ha) in Kuala Brang, ,malaysia since 1971. They are grown in rotation with rice or maize under village level technology. using minimum amount of fertilizer nitrogen. To monitor changes in total soil N and the amount of N removed by crops and weeds, the Soil Science Department, Universiti Pertanian Malaysia in collaboration with Ihe local Farmers Organisation Authority, set up a small pilot research proiect The amount of N removed by groundnuts and weeds and the level of soil N at the end of one cropping {phase were estimatcd from cropped and uncropped control plots. Any average of 130, 60 and 46 kg N.ha-' and Crop was removed from plot Sown to groundnuts as stubbles, unshelled nuts and weeds respectively, while 12 kg N was obtained from weeds in control plots. The total soil N (0-15 cm) was estimated lobe 1080 kg N. for groundnut plots and 1480 kg N ha-' for control plot. The significane of these data is discussed in relation to the overall N economy of the system operating the village level technology in Malaysia.